Clinical Characteristics of Patients with co-Existent Diabetic Peripheral Neuropathy and Depression: A Systematic Review - Zafeiri, Maria; Tsioutis, Constantinos; Kleinaki, Zoe; Manolopoulos, Philip; Ioannidis, Ioannis; Dimitriadis, George (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objectives Both diabetic peripheral neuropathy and depression have significant implications on patients’ quality of life, management and outcomes. We aimed to evaluate all available evidence concerning patients with co-existent diabetic peripheral neuropathy and depression, and describe their clinical characteristics, in order to promote early recognition and management.Methods Systematic search of PubMed for studies providing data on patients with diabetic peripheral neuropathy and depression. The primary outcome was to evaluate all available evidence related to characteristics of diabetes, diabetic peripheral neuropathy and depression. Secondary study outcomes included comorbid conditions and complications in these patients.Results Final analysis included 24 studies with data on 205 patients. Most patients were adults between 18–65 years of age. Mean HbA1c value was above 8% and most patients were treated with insulin. Neuropathy was predominantly painful and most patients with available data were considered to have major depressive disorder. In addition to diabetic peripheral neuropathy and depression, diabetes-related complications were recorded in 43 patients, the most common being autonomic neuropathy, retinopathy and nephropathy. The most frequently reported comorbidities were weight loss (72 patients), impotence (60 patients), hypertension (23 patients) and coronary artery disease (22 patients).Conclusions The present study describes the characteristics of patients with co-existent diabetic peripheral neuropathy and depression, aiming for prompt detection, prevention of further deterioration and improvement of patient outcomes. Available evidence shows that the majority of these patients are adults, with painful peripheral neuropathy and with insulin-treated and inadequately controlled diabetes.
Keywords: diabetes mellitus; diabetic peripheral neuropathy; depression; complications